Article Review Karakteristik Pasien ISPA Pada Balita Di Puskesmas Sudiang Raya - Andi Muhammad Fadilah Mursyid (Yayasan Citra Cendekia Celebes, 2021)
ABSTRACTBackground: Acute Respiratory Infections (ARI) is a health problem that exists in developing and developed countries. Research Objectives: The purpose of this study was to determine the characteristics of ARI patients in children under five at Sudiang Raya Public Health Center. Methods: The study was a descriptive study using an observational approach to describe the characteristics of ARI patients at the Sudiang Raya Community Health Center. The characteristics referred to are gender, age, nutritional status, and environmental factors. Results: From 250 people it can be seen that the number of male patients with ISPA is 124 (49.6%) and the number of female patients with ARI is 126 people (50.4%). The number of children over 5 years was 68 (27.2%). Meanwhile, the number of children aged 3-5 years was 90 (36.0%) and patients under 3 years old were 92 (36.8%). The number of child patients who experienced good nutrition was 52 (20.8%). While the number of children with malnutrition was 112 (44.8%) and 86 children with bad nutrition(34.4%). It is known that there are 194 smokers in the family (77.6%). . Meanwhile, there are no smokers in the family of 56 people (22.4%). Conclusion: By referring to the results obtained, it can be said that not only by using drugs can control ARI cases in children under five, but controlling for several risk factors can also reduce the incidence of ARI in toddlers.